Animação cultural afrobrasileira : o caso do Museu Afro Brasil - Santos, Silvana dos (2014)
This research verified the presence of Afro-Brazilian content as a methodological in the educative animation (an education through leisure) in which the theme is Afro-Brazilian. This study was developed at Afro-Brazil Museum, a place filled with educational interventions related to the Afro-Brazilian culture. Thus, the aim of this study is to outline the education through leisure by the animations showed at the Afro-Brazil Museum. In order to reach the main aim, mainly the Afro-Brazilian social practices were described with emphasis in understanding these practices, as well as the role of people involved in a situation of education through leisure at the museum. The corpus of this study is composed by six educators and a pedagogical coordinator who promote the educative animation at the museum as part of exhibition, also workshops were offered, the public was very diversified (teacher, students, common visitors, group of visitors, children, adolescents and adults). For the collection of the data we made observations, wrote diaries and also made a interview previously prepared. The study found that the approaches of Afro-Brazilian cultural manifestations are ways to deconstruct stereotypes and preconceived ideas sometimes encode the actions of the subject. Thus, the attempt to act/intercede with little discussed contents favour the conceptual contradictions, making the appropriation of the main content that are not socially established, the example of Eurocentrism. Thus, the educational activities of the Afro-Brazil Museum can be related to leisure, having the methodological principle these cultural events, since the modus operandi of the Afro-Brazil Museum, from its interventions allow reflections on culture and the senses/ meanings of a people, promoting recognition, valuing and preserving the cultural heritage of Brazil, African and Afro-Brazil, and, yet, can be considered an affirmative action. In this respect, the educational activities of the Museum can be characterized as a breakthrough in how we assign animation in this institution, because the shares offered by educators affect motivations and reflections beyond what is already known, promoting dialogue between the known/unknown.